2014
DOI: 10.1007/s10522-014-9542-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of social networks: the example of obesity

Abstract: The present paper deals with the effect of the social transmission of nutrition habits in a social and biological age-dependent context on obesity, and accordingly on type II diabetes and among its complications, the neurodegenerative diseases. The evolution of social networks and inside a network the healthy weight of a person are depending on the context in which this person has contacts and exchanges concerning his alimentation, physical activity and sedentary habits, inside the dominant social network in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The analysis of user interaction reveals the user interaction patterns in the sale campaigns, which makes it possible to differentiate the sale campaigns from other tobacco-related content. Meanwhile, the research progress in other field such as the research about obesity 42 43 44 could be applied to tobacco-related research to reveal the spreading and evolution of tobacco-related social works.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of user interaction reveals the user interaction patterns in the sale campaigns, which makes it possible to differentiate the sale campaigns from other tobacco-related content. Meanwhile, the research progress in other field such as the research about obesity 42 43 44 could be applied to tobacco-related research to reveal the spreading and evolution of tobacco-related social works.…”
Section: Discussionmentioning
confidence: 99%
“…Since decades, researches in discrete mathematics and fundamental computer science have put the emphasis on the modelling abilities of automata networks concerning interaction networks. In particular, since their introduction in the works of McCulloch and Pitts [31] and Kauffman [29,28], Boolean automata networks (bans for short) have been at the centre of numerous studies in the field of biological networks modelling, like neural networks [20,24,25,21,9,8], genetic regulation networks [30,43,44,41,32,4,36] and more recently social networks [16,12]. This can be easily explained by their very high level of abstraction that makes them ideal objects to capture formally the essence of interactions and to focus on qualitative aspects of their dynamics (e.g., the information transmissions).…”
Section: Introductionmentioning
confidence: 99%
“…The psychological factors identified in the literature are mood welfare [63], self-assessment [78,79], anxiety [80], stress [81], self-esteem [82], impulsivity [27,45,83] and self-perception of body weight [10,25,35,41,63,82,[84][85][86][87][88][89][90]. In [27], the authors conclude that personality traits are associated with weight gain, and weight gain can also be associated with a change in personality.…”
Section: Psychological and Behavioral Factorsmentioning
confidence: 99%
“…In [86], it is shown that an accurate weight perception in overweight people was associated with an increased frequency of disordered eating habits. In [89], the authors have found that the highest levels of perceived weight were obtained in individuals who are underweight and that older men and younger women classified themselves properly, as well as men without children and also women with children.…”
Section: Psychological and Behavioral Factorsmentioning
confidence: 99%